Multikulural Islam dan Budaya Lokal Indonesia - Bahri, Syamsul; Hidayat, Rahmat; Khudri, Nur Sa'adah (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2024)
The purpose of this study is to examine how most Indonesians see Islam as their religion, based on multicultural perspectives. Subsequently, explain how Islam interacts with the indigenous Indonesian culture. This study examines the literature using descriptive qualitative methodologies. The Miles and Huberman model is cited in the data analysis technique. The study's findings support that Islam, as rahmatan lil'alamin, accepts diversity in social life, as demonstrated by the Prophet Muhammad SAW's example in the Medina Charter. The idea that Islam and local culture may coexist peacefully with their respective values—that is, religious and traditional values that have been assimilated and come into direct contact—is strengthened in Indonesia by meeting Islam and tradition throughout the archipelago. Society views both as valuable assets that need to be valued and preserved. Hence, this demonstrates that the two have a harmonious relationship in which they both give rise to an Islamic trait that interacts and adapts to give rise to the internalization of Islamic principles based on indigenous knowledge in areas such as politics, law, art, architecture, and other spheres of life. The native cultures of Sumatra, Java, Sulawesi, Lombok, and Papua are examples of this internalization product